Pengalaman Spiritual Neurosains Peziarah pada Wisata Religi di Tulungagung - Ihsani, Fathul; Mufidah, Aini (Indonesian Journal of Humanities and Social Sciences, 2024)
The intersection of spirituality and neuroscience is a growing area of research that examines the impact of spiritual practices on the brain. This study focuses on the connection between spiritual experiences and neuroscientific perspectives, explicitly concerning pilgrimage tradition among Indonesian Muslims. The research aims to bridge the gap between science and spirituality and provide insights into how spiritual practices influence brain function and human behavior. This study uses a qualitative approach with a multi-site study type with interactive data analysis at the tombs of Sunan Kuning and Syekh Basarudin in Tulungagung. The data source comes from the results of interviews with the caretakers of the tombs and pilgrims. The results of this study found several spiritual experiences of pilgrims that increased faith and closeness to Allah. These experiences consist of five aspects of spiritual experience: connection, joy transcendent sense of self, divine guidance, perception of divine love, and divine help. In conclusion, this research highlights the overlapping between spiritual practices and neuroscientific insights, showing how they can shape brain function and enhance well-being. Integrating neuroscientific approaches with spiritual understanding could lead to innovative strategies in mental health therapy.